Analisis Kuat Tekan Beton Dengan Menggunakan Material Lokal Dari Kaledupa Kabupaten Wakatobi - Muhammad Muhsar; Hujiyanto Hujiyanto; Suratman Aldin (Sultra Civil Engineering Journal (SCiEJ), 2026)
The Kaledupa subdistrict, located within the Wakatobi National Park, is a marine and coastal conservation area that restricts the use of construction materials. This condition necessitates a technical study on the sustainable use of local materials. This study aims to analyze the physical characteristics of coarse and fine aggregates from Kaledupa and fine aggregates from Malaoge, as well as to compare the compressive strength of concrete using local materials and aggregates from outside the region. The research was conducted experimentally with a planned concrete quality of fc' 20 MPa. The tests included aggregate characteristics based on SNI standards and compressive strength tests on 18 cylindrical test specimens at 7, 14, and 28 days of age. The test results showed that coarse aggregates from Kaledupa met the requirements, while fine aggregates from Kaledupa did not meet the standards due to their low specific gravity and high mud content (15.22%). Fine aggregates from Malaoge also did not meet the requirements for apparent specific gravity and high water absorption (3.88%). Compressive strength tests showed that concrete with fine aggregate from Kaledupa had higher compressive strength at all testing ages, namely 14.91 MPa (7 days), 20.48 MPa (14 days), and 22.93 MPa (28 days), compared to concrete with fine aggregate from Malaoge fine aggregate, which was 11.32 MPa, 13.87 MPa, and 17.17 MPa